2014
DOI: 10.3390/rs6098190
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Global Soil Moisture Product from Finer Spatial Resolution SAR Data and Ground Measurements at Irish Sites

Abstract: Abstract:In the framework of the European Space Agency Climate Change Initiative, a global, almost daily, soil moisture (SM) product is being developed from passive and active satellite microwave sensors, at a coarse spatial resolution. This study contributes to its validation by using finer spatial resolution ASAR Wide Swath and in situ soil moisture data taken over three sites in Ireland, from 2007 to 2009. This is the first time a comparison has been carried out between three sets of independent observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 65 publications
(80 reference statements)
6
39
0
Order By: Relevance
“…Yet, despite its broad importance, field-scale soil moisture data are often not available or closest neighbor values are used when modeling hydrological and biochemical processes or when calibrating regional-scale predictions generated by complex agroecosystem models. This is, in part, due to constraints and limitations in acquiring and assembling such data over large regions and across sufficient time-periods; the acquisition process is not only costly, but labour intensive, and has high variability when upscaled from the field, to landscape, up to the regional-scale [4][5][6]. Instead of relying on direct soil moisture information validated against remote-sensing data, auxiliary predictions are often substituted based on indirect, interpolative or extrapolative assumptions that may not be statistical accurate, nor readily verifiable.…”
Section: Challenges In Modeling Soil Moisture Using Satellite Remotementioning
confidence: 99%
“…Yet, despite its broad importance, field-scale soil moisture data are often not available or closest neighbor values are used when modeling hydrological and biochemical processes or when calibrating regional-scale predictions generated by complex agroecosystem models. This is, in part, due to constraints and limitations in acquiring and assembling such data over large regions and across sufficient time-periods; the acquisition process is not only costly, but labour intensive, and has high variability when upscaled from the field, to landscape, up to the regional-scale [4][5][6]. Instead of relying on direct soil moisture information validated against remote-sensing data, auxiliary predictions are often substituted based on indirect, interpolative or extrapolative assumptions that may not be statistical accurate, nor readily verifiable.…”
Section: Challenges In Modeling Soil Moisture Using Satellite Remotementioning
confidence: 99%
“…For example, Zeng et al (2015) found the ECV SM product to be highly related to in-situ data from two different soil moisture networks at the Tibetan Plateau, with the highest R values (0.70 -0.85) and smallest ubRMSD values (0.034 -0.042m 3 m -3 ) compared to six other satellite derived soil moisture products (AMSR-E (NASA product), AMSR-E (JAXA product), AMSR-E (LPRM product), AMSR-2, ASCAT, and SMOS). Similarly, Pratola et al (2014) found strong correlations (R = 0.72 -0.88) and associated low ubRMSD values (0.05 -0.06) between ECV SM and SAR-derived soil moisture values across three grassland sites in Ireland.…”
Section: Ecv Soil Moisture Observationsmentioning
confidence: 99%
“…The ECV SM product has been validated across different regions using in-situ, model and SAR-derived soil moisture datasets in previous studies (e.g. Albergel et al, 2013b;Loew et al, 2013;Dorigo et al, 2015;Pratola et al, 2014;Zeng et al, 2015) where good agreement between the datasets was generally found. For example, Zeng et al (2015) found the ECV SM product to be highly related to in-situ data from two different soil moisture networks at the Tibetan Plateau, with the highest R values (0.70 -0.85) and smallest ubRMSD values (0.034 -0.042m 3 m -3 ) compared to six other satellite derived soil moisture products (AMSR-E (NASA product), AMSR-E (JAXA product), AMSR-E (LPRM product), AMSR-2, ASCAT, and SMOS).…”
Section: Ecv Soil Moisture Observationsmentioning
confidence: 99%
See 2 more Smart Citations